Plan de negocio para la implementación de una empresa comercializadora de ropa brasileña en el cantón Quevedo, año 2013 - Fernández Miño, Freddy José (2015)
Nowadays provenance learning as making a business plan for a company of Brazilian Clothing in Canton Quevedo establishing , developing the idea through a business plan where strategies are set to meet the different objectives of the plan. With the practice of this proposal the reason for the development of business idea , what are the steps to make it happen , what the benefits are , and who would enjoy such benefits in the canton de Quevedo by a consecutive order where the research is known experience and achieve business interest in funding and supporting research projects, the success of companies depends on the progress of human talent and creativity of enterprises and establishing actions necessary to formalize and finalize the form or method of communication, attention to satisfy the desires of customers for buying clothes and disclose all characteristics and competitive advantages of this service, the Quevedo Canton is one of the commercial cities of the country and it is located in the country by which you can get from different points, TUDO BEM is a business idea for a company of Brazilian Clothing in Canton Quevedo , embodied in a business plan to present the company attributes to citizenship Quevedeña . This idea seeks love the customer with an innovative service providing citizens a new way to buy clothes, required Financing of Brazilian trading company clothing is $ 29.921.61, 100 % was financed by a loan from National Capital Finance Corporation with an active rate of 10.5 % and whose debt is amortized over 5 years, the financial evaluation showed that Brazilian trading company in Canton Quevedo clothes have a internal rate of return of 580 % and NPV of $ 677.076.63 and the cost benefit ratio of 0.45 cents of profit for every dollar invested which is very favorable for our company